Probing hot gas around luminous red galaxies through the Sunyaev–Zel'dovich effect. Issue 2 (7th November 2019) - Tanimura, Hideki; Hinshaw, Gary; McCarthy, Ian G; Van Waerbeke, Ludovic; Aghanim, Nabila; Ma, Yin-Zhe; Mead, Alexander; Tröster, Tilman; Hojjati, Alireza; Moraes, Bruno
ABSTRACT: We construct the mean thermal Sunyaev–Zel'dovich (tSZ) Comptonization y -profile around luminous red galaxies (LRGs) in the redshift range 0.16 < z < 0.47 from the Sloan Digital Sky Survey Data Release 7 using the Planck y- map. We detect a significant tSZ signal out to ∼30 arcmin, which is well beyond the 10 arcmin angular resolution of the y- map and well beyond the virial radii of the LRGs. We compare the measured profile with predictions from the cosmo-OWLS suite of cosmological hydrodynamical simulations. The best agreement is obtained for models that include efficient feedback from active galactic nuclei, over and above feedback associated with star formation. We also compare our results with predictions based on the halo model with a universal pressure profile giving the y -signal. The predicted profile is consistent with the data when using stacked weak lensing measurements to estimate the halo masses of the LRGs, but only if we account for the clustering of neighbouring haloes via a two-halo term.